Absorption and clouds losses for Ku-and Ka-band satellite communication links - Velayutham Renganathan (2008)
The rapid growth of satellite services using higher frequency bands such as Ku and Ka has highlighted the need for estimating the propagation factors that are normally negligible at lower frequency bands. Rain attenuation is considered the dominant factor for frequencies above 1 0GHz. However, many projected higher frequency services will use very small terminals with low fade margin i.e. higher unavailability. For higher unavailability rainfall rate is lower. Therefore rain attenuation for specified availability is smaller. Hence it is necessary to identify and predict the impact of every significant attenuating effect along any given path. Water vapour absorption is one of the components that need to be characterized for low availability links.